Is there a causal association between gestational diabetes mellitus and immune mediators? A bidirectional Mendelian randomization analysis - Ji, Zhangxin; Zhang, Chenxu; Yuan, Jingjing; He, Qing; Zhang, Xinyu; Yang, Dongmei; Xu, Na; Chu, Jun (Frontiers in Endocrinology, 2024)
Diabetes that only appears or diagnoses during pregnancy is referred to gestational diabetes mellitus (GDM). The maternal physiological immune profile is essential for a positive pregnancy outcome. However, the causal relationship between GDM and immunophenotypes is not fully defined.Based on the high-density genetic variation data at a genome-wide level, we evaluated the logical associations between 731 specific immune mediators and GDM using bidirectional mendelian randomization (MR). The inverse variance weighted (IVW) employed as the main method for MR analysis. We performed multiple methods to verify the robustness and dependability of MR results, and sensitivity measures were applied to rule out potential heterogeneity and horizontal pleiotropy.A substantial causal association between several immune mediators and GDM was detected. After FDR testing, HLA DR++ monocyte %leukocyte and HLA DR on plasmacytoid DC were shown to increase the risk of GDM; in contrast, CD127 on CD28+ CD45RA+ CD8br and CD19 on PB/PC were shown to attenuate the effect of GDM. Moreover, the progression of GDM has been shown to decrease maternal levels of CD39+ activated Treg AC, CD39+ activated Treg %CD4 Treg, CD39+ resting Treg AC, CD39+ resting Treg %CD4 Treg and CD39+ CD8BR %T cell.Our findings support a possible causal association between GDM and various immunophenotypes, thus facilitating the provision of multiple options for preventive recognition as well as diagnostic and therapeutic management of GDM in clinical practice.